Этнометодология в контексте становления - Чернова, И. (Социология: теория, методы, маркетинг, 1999)
Just after appearence of ethnomethodology this branch of sociology has been considered as one without perspectives. However ethnomethodology is the treasury of ideas, which can manage study of social reality to the new level of understanding. Analysis of origination context of ethnomethodology will help to conceive ethnomethodological principles, approaches and methods to social reality study.